Penurunan Kadar Glukosida Sianogenik Biji Koro Benguk (Mucuna Pruriens, d.c.) oleh Aktivitas Fermentasi Aspergillus Oryzae, A. Sojae, Rhizopus Oligosporus dan R. Oryzae.... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
Aspergillus oryzae, A. sojae, Rhizopus oligosporus and R. oryzae have been used as inoculants for fermentation of velvet beans (Mucuna pruriens). The degradation of cyanogenic glucoside during fermentation was evaluated by measuring the concentration of HCN in the fermented beans. The results showed that the longer the fermentation, the lower cyanogenic glucoside content, suggesting that the molds have the 13-glucosidase activities. It was also found that the I1-glucosidase activity of Aspergillus spp. was higher than that of Rhizopus spp.